Body size, physical activity and risk of colorectal cancer with or without the CpG island methylator phenotype (CIMP). - Laura A E Hughes (Public Library of Science (PLoS), 2011)
Background We investigated how body size and physical activity influence the risk of the CpG island methylator phenotype (CIMP) in colorectal cancer (CRC). Methods In the Netherlands Cohort Study (n = 120,852), risk factors were self-reported at baseline in 1986. After 7.3 years of follow-up, 603 cases and 4,631 sub-cohort members were available. CIMP status according to the Weisenberger markers was determined using methylation specific PCR on DNA from paraffin embedded tumor tissue. Hazard rate ratios (HR) and 95% confidence intervals for CIMP (27.7%) and non-CIMP (72.3%) tumors were calculated according to BMI, BMI at age 20, BMI change, trouser/skirt size, height, and physical activity. Results BMI modeled per 5 kg/m(2) increase was associated with both CIMP and non-CIMP tumors, however, HRs were attenuated when additionally adjusted for trouser/skirt size. Trouser/skirt size, per 2 size increase, was associated with both tumor subtypes, even after adjustment for BMI (CIMP HR: 1.20, 95%CI: 1.01-1.43; non-CIMP HR: 1.14, 95%CI: 1.04-1.28). Height per 5 cm was associated with both tumor sub-types, but HRs were attenuated when adjusted for body weight. BMI at age 20 was positively associated with increased risk of CIMP tumors and the association was significantly less pronounced for non-CIMP tumors (P-heterogeneity = 0.01). Physical activity was inversely associated with both subtypes, but a dose-response association was observed only for non-CIMP tumors (P-trend = 0.02). Conclusions Body size, especially central adiposity, may increase the risk of both CIMP and non-CIMP tumors. Body fat at young age may differentially influence risk. Physical activity appears to decrease the risk of CRC regardless of these molecular subtypes.